The Effect of Stationary Bicycling Exercise on Thigh Muscles Strength in Postoperative Anterior Cruciate Ligament Reconstruction Rehabilitation - Junhom, Narong; Toovichian, Narumon; Penkitti, Porntip; Lertwanich, Pisit (Journal of Health Science of Thailand, 2018)
Thigh muscles strengthening plays a crucial role in rehabilitation after arthroscopic assisted anterior cruciate ligament reconstruction. Stationary bicycling is a frequently used method in postoperative rehabilitation program. However, some patients cannot use this exercise machine in their programs. The objectives of this study were to compare quadriceps ratio and to compare hamstrings ratio at 12 weeks after anterior cruciate ligament reconstruction between the patients who used stationary bicycling exercise and the patients who did not use stationary bicycling in their postoperative rehabilitation programs with studentีs t-test. The patients underwent anterior cruciate ligament reconstruction, during January to December 2007, were measured the quadriceps and hamstrings ratios with a dynamometer preoperatively and 12 weeks postoperatively. There were 16 patients using stationary bicycling exercise and 6 patients who did not use stationary bicycling in their postoperative rehabilitation programs. Twelve weeks postoperatively, the group of patients who used the stationary bicycling had mean quadriceps ratio 57.7 percent and mean hamstring ratio 96.2 percent. Whereas the group that did not use stationary bicycling had mean quadriceps ratio 54.0 percent and mean hamstring ratio 96.0 percent. This study did not found statistical significant difference in postoperative quadriceps and hamstrings ratio between the patients using stationary bicycling and the patients who did not use the stationary bicycling. With limitations in number of the participants and grouping method, further randomization study is recommended.